Regulation of Human PAX6 Expression by miR-7. (January 2014) - Needhamsen, Maria; White, Robert B.; Giles, Keith M.; Dunlop, Sarah A.; Thomas, Meghan G.
The paired box gene 6 ( PAX6 ) is a powerful mediator of eye and brain organogenesis whose spatiotemporal expression is exquisitely controlled by multiple mechanisms, including post-transcriptional regulation by microRNAs (miRNAs). In the present study, we use bioinformatic predictions to identify three candidate microRNA-7 (miR-7) target sites in the human PAX6 3′ untranslated region (3′-UTR) and demonstrate that two of them are functionally active in a human cell line. Furthermore, transient transfection of cells with synthetic miR-7 inhibits PAX6 protein expression but does not alter levels of PAX6 mRNA, suggesting that miR-7 induces translational repression of PAX6. Finally, a comparison of PAX6 3′-UTRs across species reveals that one of the functional miR-7 target sites is conserved, whereas the second functional target site is found only in primates. Thus, the interaction between PAX6 and miR-7 appears to be highly conserved; however, the precise number of sites through which this interaction occurs may have expanded throughout evolution.